IMPLEMENTATION OF THE 2023 DRINKING WATER GRANT PROGRAM BY PERUMDA TIRTANADI IN PATUMBAK VILLAGE, KAMPUNG PATUMBAK DISTRICT, DELI SERDANG REGENCY - Muhammad Harry Rahmad; Agus Suriadi; Tengku Irmayani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the implementation of the 2023 Drinking Water Grant Program by the Regional Public Company (Perumda) Tirtanadi in Patumbak Kampung Village, Patumbak Sub-district, Deli Serdang Regency. The study aims to analyze the program implementation process and identify the inhibiting and success factors. The research employs a qualitative descriptive method with data collected through in-depth interviews with seven key informants representing various levels of implementers and beneficiaries, complemented by supporting documentation. The theoretical framework refers to Charles O. Jones's (1996) policy implementation model, emphasizing three main aspects: organization, interpretation, and application. The findings indicate that, overall, the drinking water grant program was successfully implemented, achieving 38 targeted household connection points (SR) in Patumbak Kampung Village. The organizational aspect demonstrated good coordination between Perumda Tirtanadi and related parties such as the Ministry of Public Works and Housing (PUPR), Ministry of Finance, Financial and Development Supervisory Agency (BPKP), Inspectorate, Regional Development Planning Agency (Bappeda), local government, and village apparatus. However, a major challenge was the limited field technical personnel who had to serve seven regencies/cities simultaneously, causing delays in some implementation points. The interpretation aspect, through intensive socialization and policy elaboration, was well conducted, although some residents still did not fully understand the program's criteria and mechanisms. The application aspect showed positive results with strictly verified household connections and significant impacts on improving access to safe drinking water, reducing waterborne diseases, saving household costs, and enhancing community quality of life. Inhibiting factors included unclear criteria among some community members, limited human and financial resources, administrative obstacles, and the need to strengthen inter-agency coordination. Key success factors were clear standards and policy objectives, adequate resources, effective organizational structure, intensive communication and socialization, active community participation, sufficient implementer capacity, policy adaptation to local conditions, and continuous monitoring and evaluation. The study recommends enhancing community socialization and education, increasing and training field technical personnel, strengthening inter-agency and internal coordination within Perumda, simplifying administrative procedures, and developing post-installation monitoring and maintenance systems to ensure program sustainability. This study contributes significantly to the evaluation and improvement of drinking water grant programs and the development of public policy at the local level.